Struktur Komunitas Capung Dan Capung Jarum Di Sungai Gajah Wong Segmen Perkotaan Daerah Istimewa Yogyakarta - Mokhamad Nur Zaman; Bakhtiar Fahmi Fuadi; Muhammad Luthfika (Departmet of Biology, Universitas Islam Negeri Sunan Kalijaga, 2022)
Dragonflies play an important role in controlling other insect populations in nature, and are also natural indicators of environmental cleanliness. This study aims to reveal the population of dragonflies in the Gajah Wong river in urban areas in Yogyakarta. The method of determining the research area is to use transects following the river flow, and dividing the research area into 8 locations. The length of each observation site is adjusted to the distance between the large bridges that cross the top of the river. The results showed that there were 16 types of ordinary dragonflies and 9 types of dragonflies found there. The species with the highest number was Pseudagrion rubriceps as many as 255. and the least species was Gynacantha subinterrupta, Onycothemis culminicola, Ischnura senegalensis, Pseudagrion microcephalum, each found only 1 individual. An interesting finding was the presence of 2 types of Javan endemic dragonflies that were recorded along the research site.